1999
DOI: 10.1002/(sici)1097-4636(1999)48:4<540::aid-jbm21>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemical and mechanical properties of dental composites

Abstract: Composite materials were aged in distilled, deionized water and a solution by volume of 50% distilled, deionized water and 50% ethanol for three mon at 37 degrees C. Also investigated was the effect of aging dental glass filler powder in distilled, deionized water for one, three, six, and ten mon at 2 degrees C, 37 degrees C, and 72 degrees C. Atomic absorption analysis was performed on the aqueous media in which the samples were aged in order to determine the extent of leaching of silicon and strontium. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
0
8
0
3
Order By: Relevance
“…[2][3][20][21][22] Some previous studies found that the release of particular filler particles, such as strontium or barium, were different after aging in ethanol, artificial saliva and distilled water. 4,[23][24] However, as only little correlation has been observed between filler leaching and flexural strength, Drummond and others assumed that the deterioration of dental composites is more closely related to degradation of the resin matrix and the matrix-filler bonds than degradation of the glass fillers, 25 which is in accordance with other reports. 20 Zhang reported that storage of specimens in a mixture of ethanol and water led to a significantly higher decrease in FS than did immersion in distilled water or artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][20][21][22] Some previous studies found that the release of particular filler particles, such as strontium or barium, were different after aging in ethanol, artificial saliva and distilled water. 4,[23][24] However, as only little correlation has been observed between filler leaching and flexural strength, Drummond and others assumed that the deterioration of dental composites is more closely related to degradation of the resin matrix and the matrix-filler bonds than degradation of the glass fillers, 25 which is in accordance with other reports. 20 Zhang reported that storage of specimens in a mixture of ethanol and water led to a significantly higher decrease in FS than did immersion in distilled water or artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, improved filler-matrix coupling via silanization 33) is at the expense of surface modification of the glass fillers that results in a delay in the ion leaching process 34) . Deterioration of the filler-resin matrix interface may also occur rapidly following water sorption 35,36) , owing to the formation of siliceous hydrogel layers around the ion-leachable glass fillers.…”
Section: Optimization Of Prg-ca Filler Content In Light-cured Adhesivementioning
confidence: 99%
“…Moreover, improved filler-matrix coupling via silanization 33) is at the expense of surface modification of the glass fillers that results in a delay in the ion leaching process 34) . Deterioration of the filler-resin matrix interface may also occur rapidly following water sorption 35,36) , owing to the formation of siliceous hydrogel layers around the ion-leachable glass fillers.Such a scenario probably accounted for the change in flexural properties of compomers after water storage 36) . By contrast, the use of silanized PRG fillers permits better coupling between dehydrated hydrogel and the resin matrix.…”
mentioning
confidence: 99%
“…The inorganic particles constitute 70-80 wt % of the composite and glass-ionomer materials. 1 Typical composition of the filler particles is crystalline quartz or barium glass in composites 2 and fluoroaluminosilicate glass in glass-ionomer materials. 3 In dental composite and compomer materials, the inorganic filler particles are embedded in a resin matrix, whereas the glass-ionomer reaction is a partial dissolution of the glass fillers by polyalkenoic acids, forming siliceous hydrogel layer on the surface of the glass particles and a matrix of metal ions bound to the polyacid chains.…”
Section: Introductionmentioning
confidence: 99%
“…The glass filler leaches out of the composite material, which results primarily from a breakdown in the bond between the filler and the matrix. 1 Material degradation results in exposure of the patient to leachables, including particles, either local close to the restoration or systemic after absorption from the gastrointestinal tract. In evaluating the toxicity of dental biomaterials, emphasis has been put on the resin part 7,8 even though it is known from other application that particles of comparable composition and size have potential for biological effects.…”
Section: Introductionmentioning
confidence: 99%